A worldwide cost-based design and optimization of tilted bifacial solar farms. (1st August 2019) - Patel, M. Tahir; Khan, M. Ryyan; Sun, Xingshu; Alam, Muhammad A.
Highlights: A new perspective on LCOE that decouples cost and performance of solar farms. Optimization of solar farm design using essential Module to Land cost ratio ( M L ). Modeling of direct, diffuse, and albedo light collection for tilted bifacial PV. 2–6% reduction in LCOE for bifacial over monofacial PV farm for |latitude| > 30°. Global maps, opportunities, and challenges for bifacial vs. monofacial PV farm. Abstract: The steady decrease in the levelized cost of solar energy (LCOE) has made it increasingly cost-competitive against fossil fuels. The cost reduction is supported by a combination of material, device, and system innovations. To this end, bifacial solar farms are expected to decrease LCOE further by increasing the energy yield; but given the rapid pace of design/manufacturing innovations, a cost-inclusive optimization of bifacial PV systems at the farm-level (including land costs) has not been reported. In our worldwide study, we use a fundamentally new approach to decouple energy yield from cost considerations by parameterizing the LCOE formula in terms of "land-related cost" and "module-related cost" to show that an interplay of these parameters defines the optimum design of bifacial farms. For ground-mounted solar panels, we observe that the panels must be oriented horizontally and packed densely for locations with high "land-related cost", whereas the panels should be optimally tilted for places with high "module-related cost". For systems with relatively high "module-related costs" and for locations with |latitude| > 30°, the bifacial modules must be tilted ∼10°–15° higher and will reduce LCOE by 2–6% compared to their monofacial counterparts. The results in this paper will guide the deployment of LCOE-minimized ground-mounted tilted bifacial farms around the world.